Correlation of education factors and knowledge in choosing places to give birth in the work area of the Rokan IV Koto I health center - Fitria Rahmi; Handayani Eka Yuli; Wulandari Sri; Syari Mila; Sinaga Elvina Sari (BIO Web of Conferences)
The purpose of this study is to determine the factors influencing pregnant women’s delivery place preferences. The study emphasizes the significance of choosing safe delivery options, as required by the Indonesian government, and making sure mothers give birth in medical facilities that have enough resources and qualified staff, especially in case of emergencies. Inappropriate clinic or assistant selection by family members may put the health of the mother and the newborn at risk. An observational approach was used in a cross-sectional design. Written questionnaires were used to gather primary data, and the chi-square test was used for analysis. The study’s population consisted of all pregnant women at Rokan IV Koto Health Care Center, including 80 women who gave birth in 2022. Knowledge (p=0.000) and education (p=0.002) were found to be positively correlated with the likelihood of selecting an appropriate delivery facility. Support from family members, however, did not significantly correlate. These findings highlight how knowledge and education affect decisions about safe birthing. Healthcare facilities should step up efforts to spread knowledge and raise awareness about the value of giving birth in well-equipped facilities with trained medical personnel in order to guarantee that all pregnant mothers have access to safe delivery services. The community’s maternal and newborn health outcomes could be greatly enhanced by this strategy.